Experience-Induced Interocular Plasticity of Vision in Infancy - Tschetter, Wayne; Douglas, Robert M.; Prusky, Glen T. (Frontiers in Systems Neuroscience, 2011)
Animal model studies of amblyopia have generally found that enduring effects of monocular deprivation (MD) on visual behavior (i.e. loss of visual acuity) are limited to the deprived eye, and are restricted to juvenile life. We have previously reported, however, that lasting effects of MD on visual function can be elicited in adulthood by stimulating visuomotor experience through the non-deprived eye. To test whether visuomotor experience would also induce interocular plasticity of vision in infancy, we assessed in rats from eye opening on postnatal day (P)15, the effect of pairing MD with daily threshold measurements of opto-kinetic tracking (OKT). Combining MD with OKT experience up to P25 led to a 60% enhancement of the spatial frequency threshold through the non-deprived eye for OKT during the MD, which was followed by loss of function ( 60% below normal) through both eyes when the deprived eye was opened. Strictly limiting the period of deprivation to infancy, by opening the deprived eye at P19, resulted in comparable loss of function. Thresholds recovered by P30 unless binocular OKT experience was stimulated through both eyes from P25-P30, which was sufficient to maintain the lost function indefinitely. The ability to generate the plasticity, as well as to maintain lost function, was dependent on visual cortex. Animals with reduced visuomotor thresholds also exhibited significantly reduced visual acuity, measured independently in a discrimination task. Thus, a form of interocular plasticity, in which the stimulation of visual experience during MD can induce amblyopia, is present before the beginning of juvenile life.